Utilization of Yellow Shells (Cypraea moneta) in the Treatment of Cadmium Heavy Metal (Cd) Waste - Noor Isnaini Azkiya; Rosita Dwi Chrisnandari; Wianthi Septia Witasari (Jurnal Teknik Kimia dan Lingkungan, 2023)
Cadmium (Cd) metal is a heavy metal that can cause environmental pollution if its levels are above the environmental quality standard value. Generally, industrial wastes such as paper industry waste contain heavy metal Cd with levels reaching 0.026 ppm. Meanwhile, the quality standard for Cd metal in the environment is 0.005 ppm. For this reason, it is necessary to process it to reduce the levels of Cd metal in the waste before being discharged into the environment. One way that can be used to reduce the levels of Cd metal is by adsorption method using Cypraea moneta clamshells containing chitin. This study used variations in the particle size of the shellfish adsorbent of 6 and 12 mesh. In addition, the ratio of the amount of adsorbate and adsorbent (mg:mg) is 1 : 0.5x106; 1 : 1x106; and 1 : 1.5x106. Based on the results obtained, it showed that the use of shellfish as an adsorbent was able to reduce Cd metal content up to 89%.